BRAF V600 mutation detection in melanoma: a comparison of two laboratory testing methods. Issue 11 (19th April 2017) - O'Brien, Odharnaith; Lyons, Tomas; Murphy, Sandra; Feeley, Linda; Power, Derek; Heffron, Cynthia C B B
Abstract : Aims: The assessment of B-raf proto-oncogene, serine/threonine kinase ( BRAF ) gene status is now standard practice in patients diagnosed with metastatic melanoma with its presence predicting a clinical response to treatment with BRAF inhibitors. The gold standard in determining BRAF status is currently by DNA-based methods. More recently, a BRAF V600E antibody has been developed. We aim to investigate whether immunohistochemical detection of BRAF mutation is a suitable alternative to molecular testing by polymerase chain reaction (PCR). Methods: We assessed the incidence of BRAF mutation in our cohort of 132 patients, as determined by PCR, as well as examining clinical and histopathological features. We investigated the sensitivity and specificity of the anti-BRAF V600E VE1 clone antibody in detecting the presence of the BRAF V600E mutation in 122 cases deemed suitable for testing. Results: The incidence of BRAF mutation in our cohort was 28.8% (38/132). Patients with the BRAF mutation were found to be significantly younger at age of diagnosis. BRAF-mutated melanomas tended to be thinner and more mitotically active. The antibody showed a sensitivity of 86.1% with a specificity of 96.9%. The positive predictive value was 96.9%; the negative predictive value was 94.4%. The concordance rate between PCR and immunohistochemical BRAF status was 95.1% (116/122). Conclusions: The rate of BRAF mutation in our cohort (28.8%) was lower than international published rates of 40%–60%. This may reflect ethnic or geographic differences within population cohorts. The high concordance rate of PCR and immunohistochemical methods in determining BRAF status suggests that immunohistochemistry is potentially a viable, cost-effective alternative to PCR testing and suitable as a screening test for the BRAF mutation.